The Trailing End Point Phenotype in Antifungal Susceptibility Testing Is pH Dependent - Marr, Kieren A. (American Society for Microbiology, 1999)
The interpretation of end points in azole antifungal drug susceptibility testing is problematic, in part due to incomplete growth inhibition of Candida species. Such trailing growth can cause the MICs of fluconazole for some isolates to be low (<1 μg/ml) after 24 h of growth but much higher (>64 μg/ml) after 48 h. Isolates having this type of growth have been described as having a low-high phenotype. Although these isolates would be considered resistant by current National Committee of Clinical Laboratory Standards definitions, growing evidence suggests that they are susceptible in vivo. To further characterize these isolates in vitro, microdilution susceptibility testing comparing the complex defined medium RPMI 1640 to a defined minimal medium (yeast nitrogen broth) was performed. Isolates having trailing growth in MOPS (morpholinepropanesulfonic acid)-buffered RPMI 1640 (pH 7.0) were found to have clear end points in the minimal medium at its native pH of 4.5. The pH of the medium influenced the low-high phenotype, as these same isolates trailed in minimal medium adjusted to a pH of ≥6.0 but did not trail in RPMI 1640 adjusted to a pH of ≤5.0. This pH effect was independent of the medium buffering capacity, as trailing was decreased in both minimal medium and RPMI 1640 (pH 4.5) buffered in citrate. Adjustment in the pH of MOPS-buffered RPMI 1640 reduced trailing in multiple strains of Candida albicans without affecting the MICs for isolates having known susceptible (low-low) and resistant (high-high) phenotypes. Adjustment of the medium pH could be considered to eliminate trailing in azole drug susceptibility testing.